Empowering Chemistry Education: Leveraging Technology to Elevate Academic Achievement at Kajaji Senior High School, Sene District, Bono East Region (International Journal of Scientific Research in Science and Technology, 2024)
This research work compares alternative methodologies; educational technology (projector media) and the traditional method of delivery, to improve upon students’ academic performance in chemistry among students of science students of Kajaji senior high school. Research questions and null hypotheses were formulated to serve as guide for this study. Form two science students were used for this study by convenience sampling and were placed into experimental and control groups. The study made use of standardized achievement test items from some selected topics in chemistry. Quasi-experimental non-randomised design involving pre-test and post-test was employed for the purpose of this study. The test scores obtained were analysed using t-test. The result obtained in this study showed that one of the null hypotheses formulated and tested at 95% level of significance was rejected. The findings revealed that the use of projector media in teaching was a more effective way of improving student’s performance in the teaching and learning of chemistry as compared to the conventional method.